Transformasi Pendidikan Indonesia Menuju Ekosistem Pembelajaran Cerdas, Inovasi, Digitalisasi, dan Penguatan Karakter di Era Global - Nurullaili Malanul Hikmah; Nurhayati Muslimah; Muktiningsih Nurjayadi; Achmad Ridwan (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
Abstract Adapting the national education system is fundamental to navigating the Industrial Revolution 4.0 and Society 5.0 eras, which prioritize the mastery of 21st-century skills. Despite the implementation of the Emancipated Learning policy, low PISA scores (OECD, 2019) underscore the urgent need for a comprehensive overhaul of the learning ecosystem that integrates technology with character strengthening to mitigate the risk of moral erosion (Lickona, 2004). This qualitative research aims to analyze and formulate a transformation strategy toward a sustainable Blended Learning Ecosystem through a Systematic Literature Review (SLR) methodology. Data were gathered from indexed scientific journals published between 2020 and 2025 and analyzed using content analysis and thematic synthesis techniques. The synthesis results indicate that an effective smart learning ecosystem requires an adaptive blended learning model based on data personalization, which is curricularly integrated with the graduate profile. This study concludes that the success of educational transformation in Indonesia depends on a harmonious tripartite synergy: technology as an instrument, innovation as a pedagogical strategy, and character as a moral foundation. This synergy is expected to produce a generation that is intellectually superior, digitally proficient, and possesses strong moral integrity on the global stage. Abstrak Penyesuaian sistem pendidikan nasional menjadi fundamental dalam menghadapi era Revolusi Industri 4.0 dan Society 5.0 yang berorientasi pada penguasaan keterampilan abad ke-21. Meskipun kebijakan